Pengaruh Kewirausahaan Terhadap Kemampuan Berkembang UMKM: Pengalaman UMKM Di Kota Waingapu Sumba Timur - Yohanes Batista Ndata Merang; Muana Nanga (JURNAL TRANSFORMATIF UNKRISWINA SUMBA, 2014)
Entrepreneurship is a well-known concept in economic knowledge for long time and has very important role in country’s development. However, this is applicable for micro, small and average business which is realized to help a business with its progress and failure. The spirit, attitude or behavior or anything related to entrepreneurship will help a business to develop. If there is no such attitude, then the business will fail (not develop well). This research focus on the influence of entrepreneurship to the ability of development micro-business (UMK) Kota Waingapu sub-district (study in a sub-district in Kota Waingapu sub-regency). Entrepreneurship in this research will focus on 3 aspects, that is, ability or innovation efforts, ability or brave to take risk and ability to take and use new opportunity.The research result shows that just the ability or brave to take risk and the ability to take and use new opportunity that have significant influence to the ability of micro-bussiness to develop well in Kamalaputih sub-district. So this thing should be maintained and improved. While the ability or innovation effort has no significant influence to the ability to develop of UMK in Kamalaputih sub-district. So UMK needs to increase its ability or innovation effort. Keywords : entrepreneurship, innovation, risk, opportunity and ability to develop